Evaluation of Total Flavonoid, Total Phenolic, and Antioxidant Activity of Etlingera elatior (Jack) R.M.Sm Flower, Fruit, and Leaf - Ulya Safrina; Wardiyah Wardiyah; Harpolia Cartika (Majalah Obat Tradisional, 2022)
Etlingera elatior (E. elatior) plant has long been used as a kitchen spice and daily food. E. elatior has potential as an antioxidant because it contains polyphenol and flavonoid compounds widely found in the leaves, fruit, and flowers. This study measures the total flavonoid content, total phenol content, and antioxidant activity using the ABTS method. Total phenol content was determined by the Follin-Ciocalteu method and total flavonoid content was determined by the Aluminium Chloride method. The results showed that the total flavonoid content from the highest to the lowest value from E. elatior was fruit extract, leaf extract, and flower extract, respectively. The value of total flavonoid content was 8.38 ± 0.15; 4.86 ± 0.10; and 2.60 ± 0.04 % w/w Catechin Equivalent (CE). The total phenol content from the highest to the lowest value from E. elatior was fruit extract, leaf extract, and flower extract, respectively. The total phenolic content values were 54.48 ± 1.89, 46.20 ± 0.83, and 4.80 ± 0.53 % w/w Gallic Acid Equivalent (GAE). The highest to lowest antioxidant activity values (IC50) were leaf extract at 58.82 ppm (strong activity), fruit extract at 103.05 ppm (moderate activity), and flower extract at 251.40 (weak activity), respectively.